PENGARUH KUALITAS LAYANAN DAN INOVASI LAYANAN TERHADAP KEPUASAN KONSUMEN PADA RUMAH SAKIT BUAH HATI KUDUS - Muslichati, Ela Zakiya; Wartini, Sri (Management Analysis Journal, 2015)
The purpose of this research is to explain influence the service quality and service innovation, partial or simultaneous to the consumer satisfaction of Buah Hati Hospital Kudus The sampling uses incidental sampling technique. The numbers of respondents are 116 respondents. The methods used to collect the data are method observation, interview method and questionnaire method. Analysis of data using multiple linier regression with SPSS version 20. The thing prove that there is the influence of the service qualityÂ  and services innovation simultaneously positive and significant on consumer satisfaction. The conclusion of this research is the service quality and service innovation influential in partial and simultaneous to consumer satisfaction. So it could be explained that the higher quality of service and improved service innovation, the consumer satisfaction steadily grew.